Reduced Consolidation, Reinstatement, and Renewal of Conditioned Fear Memory by Repetitive Treatment of Radix Polygalae in Mice - Shin, Jung-Won; Park, Hyunwoo; Cho, Yoonju; Lee, Suck; Yoon, Jiwon; Maeng, Sungho (Frontiers in Psychiatry, 2017)
The therapeutic goal for the treatment of post-traumatic stress disorder (PTSD) is to promote extinction and to prevent the relapse of fearful memories. Research has identified pharmacological treatments that may regulate the formation and extinction of fear memories, but not many reagents that block the relapse of extinguished fear are known. Radix polygalae (RP) is an Asian herb used for sedation, and its ingredients have anxiolytic and antidepressant properties. As various neurological effects have been identified, we tested whether RP affects the relapse of fear. Freezing in response to a conditioned context and cues were used to measure the effects of RP in mice. In cohort 1 (n=30), consolidation, extinction and reinstatement were tested during the course of 18 days of treatment. In cohort 2 (n=30), consolidation, extinction and renewal were tested during 10 days of treatment. The consolidation, extinction, reinstatement and possibly the renewal of context-induced freezing were inhibited due to the administration of RP in animal subjects. However, the effects of RP on the freezing responses of subjects elicited by conditioned auditory cues were less obvious. Because it effectively suppresses the consolidation of fear memories, RP may be used for primary and secondary prevention of symptoms in PTSD patients. Additionally, because it effectively suppresses the reinstatement and renewal of fear memories, RP may be applied for the prevention of fear relapse in PTSD patients who have undergone exposure therapy.